THE GENERAL LINGUISTIC STATUS OF THE CAUSATIVE CATEGORY - O’rozboyeva Mavluda Shukurlo qizi (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
This paper explores the role of the causative category in linguistic systems, emphasizing its general status in linguistic theory and its connection to cognitive processes. The causative construction, which expresses the relationship between an action and the instigator of that action, provides insight into how languages structure events and actions. It demonstrates how the manipulation of causative constructions reflects deeper cognitive frameworks related to agency, control, and responsibility. The study also highlights how causative structures can vary across languages, illustrating the influence of culture and worldview on linguistic form. The paper discusses both morphosyntactic and semantic aspects of causativity, exploring its relevance in cognitive linguistics and its impact on our understanding of action, event causation, and social dynamics.